2021
DOI: 10.1016/j.heliyon.2020.e05820
|View full text |Cite
|
Sign up to set email alerts
|

Safety of oral administration of high doses of ivermectin by means of biocompatible polyelectrolytes formulation

Abstract: The FDA-approved drug ivermectin is applied for treatments of onchocerciasis and lymphatic filariasis. The anticancer and anti-viral activities have been demonstrated stressing possibilities for the drug repurposing and therefore new information on high dosage safety is on demand. We analyzed in vivo tissue responses for high doses of ivermectin using Corydoras fish as animal model. We made intestinal histology and hematologic assays after oral administration of ivermectin transported with polyelectrolytes for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Most of the safety and pharmacokinetic data on oral administered ivermectin are from doses of 0.15–0.20 mg/kg. In an animal study by Rafael et al doses of ivermectin in the range of 0.22–0.86 mg/kg were not harmful to intestinal tissue and blood cells in general [17] .…”
Section: Discussionmentioning
confidence: 95%
“…Most of the safety and pharmacokinetic data on oral administered ivermectin are from doses of 0.15–0.20 mg/kg. In an animal study by Rafael et al doses of ivermectin in the range of 0.22–0.86 mg/kg were not harmful to intestinal tissue and blood cells in general [17] .…”
Section: Discussionmentioning
confidence: 95%
“…The structural changes established by SAXS suggested that the biopolymers were successfully incorporated to the cubosomal lipid structures, rendering the obtained nanoparticles pH-responsive vehicles. Both biopolymers have been incorporated in different types of nanoparticles [44,54,57]. However, they built-up a promising new nanostructured material in association with lipid-based cubosomes by tailoring liquid crystalline structure and poly-charged shells, which can render stronger interaction and deeper penetration in the mucosal layers of intestine.…”
Section: Discussionmentioning
confidence: 99%
“…The described pH-responsiveness, related to the structural features of the biopolymertailored cubosomes, may represent important advantages for the development of colloidal vehicles for biomedical applications where pH variation plays an important role. Previously, the combination of CHarg and ALG in the production of micro and nanoparticles as drug delivery systems has shown great potential for in vivo oral administration [54,[56][57][58][59]. Indeed, the gastrointestinal tract presents extreme pH variation to which drug delivery devices can be developed to respond in a manner to provide localized, optimized, and prolonged delivery of the carried bioactives.…”
Section: Charge Transitions In the Biopolymer Complexes Imparting Ph-responsiveness Of The Cubosome Particlesmentioning
confidence: 99%
See 1 more Smart Citation
“…One hundred and eighty adult specimens of C. schwartzi, bought from a commercial provider, were employed in similar conditions as described in our previous studies (Madrid et al, 2021;Mathews et al, 2018;Patta et al, 2020). The fish were divided into three aquariums with 15 L of dechlorinated water, previously conditioned to adequate water conditions for the species, with a constant temperature of 28°C using thermostat systems (Hopar Aquarium Heater H-606 150W), constant pH 6.8 and adjusted physicochemical parameters (Seachem Prime water conditioner), and submitted to constant filtration and aeration (Aquatech FE25 Filtration System) with the water flow rate adjusted to 250 L/h.…”
Section: Experimental Animalsmentioning
confidence: 99%